The Influence of Achievement Motivation, Learning Creativity, Digital Literacy, Library Utilization, Student Perception of Teacher Teaching Style Variation, and Learning Media Usage on the Learning Achievement of 11th Grade Students in Economics Subject - Dedeh Kurnia Ningsih; Ansofino; Jimi Ronald (Global Action and Education for Society, 2026)
Learning achievement is a key indicator of educational success. This study aims to analyze the effect of achievement motivation, learning creativity, digital literacy, library utilization, perception of teachers’ teaching style variation, and the use of instructional media on the academic achievement of grade XI students at SMAN 1 VII Koto Sungai Sarik in Economics subject. This research employed a quantitative associative approach. The population was all grade XI students totaling 190. A sample of 64 respondents was selected using stratified random sampling. The instruments used were questionnaires tested for validity and reliability, as well as documentation of Economics report card scores. Data were analyzed using multiple linear regression with SPSS and EViews. The findings show that achievement motivation, learning creativity, digital literacy, library utilization, teaching style variation, and instructional media usage significantly and positively influence learning achievement, both partially and simultaneously. The F-test value = 9.032 is greater than F-table (2.24) with significance < 0.05, and R² indicates a strong explanatory contribution.